Cross-sectional survey research investigating how medical students use clinical photographs to support their learning. (2nd January 2019) - Dakin, Carly; Coates, Elizabeth
Abstract: This study explored students' use of clinical photographs within seven medical schools in England. The design used was cross-sectional survey research. The data collection method was a self-completion online survey. A total of 283 students participated in the study. The proportion of students using clinical photographs was 87%, p = .217. The medical subject discipline in which clinical photographs were considered by students as most useful were dermatology (71%). The proportion for those 'Very' or 'Quite' likely to access an image library made available through their medical school was 92%. The main barrier to using existing photographic resources was awareness.